Records of Recovering American Marten, Martes americana, in New Hampshire - Kelly, JR; Fuller, TK; Kanter, JJ (ScholarWorks@UMass Amherst, 2009)
Recent and current distribution of state-threatened American Marten (Martes americana) in New Hampshire was identified by summarizing 157 occurrence records (1980–2004) in a database and mapped using Geographic Information Systems (GIS). Records included visual observations, snow tracks, road kill, trapper captures, systematic live-trapping locations, and other miscellaneous locations. Marten in New Hampshire are now found throughout the White Mountains north to the Canadian border, with the highest relative abundance in the very northern tip of New Hampshire. The recent expansion in the range of Martens includes reproducing females, but a sex ratio biased towards males in some areas suggests that dispersing individuals might inhabit much of the range.